1997
DOI: 10.1152/ajplung.1997.272.1.l148
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cu,Zn-SOD activity in asthmatic airway epithelium: correction by inhaled corticosteroid in vivo

Abstract: To investigate the antioxidant response of respiratory epithelium to the chronic airway inflammation in asthma, the major intracellular antioxidants [copper and zinc-containing superoxide dismutase (Cu,Zn-SOD) and manganese-containing SOD (Mn-SOD), catalase, and glutathione peroxidase] were quantitated in bronchial epithelial cells of healthy control and asthmatic individuals. Although catalase and glutathione peroxidase in bronchial epithelium of asthmatics were similar to control SOD activity in asthmatics n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
4
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 0 publications
9
111
4
6
Order By: Relevance
“…De Raeve HR et al have reported a decreased Zn-SOD activity airway and Zinc serum in children with lower respiratory tract infection. 11,12 Further Meeks-Gardner J et al have shown a positive Zinc supplementation in these patients.…”
Section: Discussionmentioning
confidence: 93%
“…De Raeve HR et al have reported a decreased Zn-SOD activity airway and Zinc serum in children with lower respiratory tract infection. 11,12 Further Meeks-Gardner J et al have shown a positive Zinc supplementation in these patients.…”
Section: Discussionmentioning
confidence: 93%
“…Hence, oxidative inactivation of CuZn SOD may also contribute to the loss of total SOD activity noted in asthma. 17,18 The loss of SOD activity likely reflects the increased oxidative and nitrative stress in the asthmatic airway, and may serve as a marker of asthma severity. In support of SOD as a surrogate marker of oxidant stress and asthma severity, Smith and colleagues 18 showed a correlation between the degree of airway reactivity to methacholine and SOD activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 Furthermore, other reports have shown that loss of SOD can initiate apoptosis in some cell types, 29 therefore we hypothesized that diminished SOD in airway epithelial cells might be a central event mediating airway epithelial cell apoptosis. To address whether inactivation of SOD and/or increasing reactive oxygen species play a role in airway apoptosis, we treated BET1A cells with pyrogallol, a superoxide-producing agent, 2-ME, a SOD activity inhibitor or hydrogen peroxide, in a dose-and time-dependent manner.…”
Section: Effects Of Oxidative Stress On Airway Epithelial Cellsmentioning
confidence: 98%
See 2 more Smart Citations